Degree of bias in polish general-information newspapers (selected determinants) - Olechowska, Paulina (Political Preferences, 2017)
This article attempts to determine the degree of bias in Polish general-information newspapers (“Gazeta Polska Codziennie”, “Nasz Dziennik”, “Gazeta Wyborcza” and “Rzeczpospolita”), based on selected determinants. They include: thematic agenda, political pluralism and media coverage, degree of directives and persuasiveness of messages. The author used the method of content analysis of press, analysis method and synthesis method. Key words: media bias, media-party parallelism, polish general-information newspapers